A Change Will Do You Good: Does Continuous Environmental Improvement Matter?. (December 2022) - Busch, Timo; Johnson, Matthew P.; Schnippering, Maximilian
Superior corporate environmental performance (CEP) is considered to be an indication of well-managed firms. While previous empirical research has operationalized various environmental measurements, one aspect has remained under-scrutinized, namely, continuous improvement. We examine whether continuous CEP improvement is reflected in aggregated environmental scores provided by sustainability rating agencies. From a natural resource-based view, we investigate the association of continuous CEP improvement with corporate financial performance (CFP). Based on panel data (2005–2020), the results show that continuous CEP improvement is not associated with aggregated environmental scores provided by three major rating agencies. At the same time, however, continuous improvement is positively associated with accounting as well as market-based CFP. The article concludes that continuous CEP improvement is relevant from a materiality perspective, but it is not adequately captured in the environmental scores from rating agencies. Therefore, we propose using a best-in-progress approach as a meaningful investment strategy instead of the established best-in-class screenings.